Illustrative presentation in formation of ESL students’ lexical skills - Mansurovich, Shangareev Mustafa; Karimova, Anna Anatolyevna; Khasanova, Oksana Vladimirovna; Shustova, Svetlana Viktorovna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The article is devoted to the problems of forming and developing lexical skills by modern multimedia means of visualization in the ESL classroom. Modern technologies have been led to new possibilities to integrate multimedia tools and means of visualization in the ESL classroom. The aim of this paper is to analyze the current ESL coursebooks and coursebook supplements and give recommendations to teachers how to use the sufficient range of means of visualization effectively. As a part of research different types of questionnaires were handed to teachers and first-year students of Bachelor’s Program "Pedagogical Education (double major) and Second Foreign language " (5 years, full time) of Kazan State University. After this, a set of classes was organized for two groups of first-year students. The outcomes have been measured with qualitative and quantitative methods. The results show that the teachers do not use means of visualization and are not ready to make them the integral part of everyday lessons due to time management issues, lack of methodical ways of organization of educational process. Due to these results it can be resumed that using multimedia means of visualization as tools in the ESL classroom is highly beneficial for students and enhanced the learning process.